Polynomial approximation of the small‐signal stability region boundaries and its credible region in high‐dimensional parameter space. (23rd March 2012) - Yang, Su; Liu, Feng; Zhang, De; Mei, Shengwei
SUMMARY: This paper presents a polynomial approximation method to give an explicit expression for the boundaries of small‐signal stability region (SSSR) based on the implicit function approach. Different from most of the current methods, the proposed method solves the problem of SSSR boundary approximation directly in the high‐dimensional parameter spaces. To settle the problem of local validity due to the polynomial approximation, we further put forward an optimization formula to estimate the credible region of the approximation with a given accuracy. The correctness and effectiveness of the proposed methods are verified through the case studies on a rudimentary power system and the real Hainan power grid of China. Copyright © 2012 John Wiley & Sons, Ltd.